2018
DOI: 10.1002/ange.201809754
|View full text |Cite
|
Sign up to set email alerts
|

Diphosphahexaarenes as Highly Fluorescent and Stable Materials

Abstract: Oligoarenes are regarded as subunits of π‐extended carbon nanoforms, such as graphene and nanotubes, with exceptional technological importance. Fused arenes can thus provide fundamental insight into the nature of the electronic properties of fused polyaromatic rings and pave the way for the design of extended graphene‐like materials. However, large π‐extended arenes often show low stability. Herein we report the straightforward preparation of linearly fused diphosphahexaarenes containing two six‐membered phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 42 publications
5
21
0
Order By: Relevance
“…For our investigations, we chose the cis-derivative 1a (Scheme 1) owing to a) its straightforward preparation, [13] b) the significant contributiono ft he phosphorus atom into the LUMO orbital, and c) its 84 %f luorescence quantum yield. As reported previously, [13] the isolation of the cis-derivative 1a involve its separation from the corresponding trans-isomer 1b by columnc hromatography.F irst, we investigated the reduction of the phosphorus centers of 1a from l 5 ; s 2 -endo, s 2 -exo [12a] to l 3 ; s 2 -endo, s 1 -exo. It is important to highlight that within heterocyclics ystems, the phosphorus atoms hardly invert due to their relativelyh igh inversion barrier.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For our investigations, we chose the cis-derivative 1a (Scheme 1) owing to a) its straightforward preparation, [13] b) the significant contributiono ft he phosphorus atom into the LUMO orbital, and c) its 84 %f luorescence quantum yield. As reported previously, [13] the isolation of the cis-derivative 1a involve its separation from the corresponding trans-isomer 1b by columnc hromatography.F irst, we investigated the reduction of the phosphorus centers of 1a from l 5 ; s 2 -endo, s 2 -exo [12a] to l 3 ; s 2 -endo, s 1 -exo. It is important to highlight that within heterocyclics ystems, the phosphorus atoms hardly invert due to their relativelyh igh inversion barrier.…”
Section: Resultsmentioning
confidence: 99%
“…[12] In 2018, our group reported the synthesis and optoelectronic properties of novel diphosphahexaarenes. [13] Indeed, the introductiono ft wo six-memberedp hosphorus heterocycles into large linearly fused arenes,i nc ombination with two off-linear benzener ings, led to an outstanding stability and remarkable solubility in common organic solvents. [13] In the context of materials science, ideal would be to conceive new arene derivativesw hose characteristics could be easily tailoredt os pecific applicationsb ym eanso ff acile postfunctionalization reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in material chemistry are closely related to the development of new synthetic methodologies and molecules. In the ever‐growing catalog of available π‐conjugated phosphacycles, the π‐fused six‐membered phosphacycles remain less developed, because of their limited synthetic protocols For examples, a simple strategy to access the π‐conjugated six membered phosphacycles frameworks is the intramolecular phospha‐Friedel–Crafts reaction with the presence of AlCl 3 , metal‐mediated direct C–H functionalization of trisubstituted phosphines provide a direct synthesis of six‐membered phosphindolium salts fused π‐extended scaffolds . Very recently, the elegantly embedding six‐membered phosphacycle into large acenes through a spatial proximity favored nucleophilic substitution of chlorophosphines was developed, which opened up new opportunities for the investigation of phosphorus‐based optoelectronic materials .…”
Section: Introductionmentioning
confidence: 99%
“…The naphthyl substituent on phosphorus is crucial to this annulation, which serves as a C3 unit and fuses with the peripheral aryl C2 moiety through phosphorus atom to form the six‐membered phosphacycles . The published preliminary results demonstrated that the six‐membered phosphacycles incorporated π‐conjugated species had tunable photo‐electronic properties and could serve as luminescent materials,[1a], [2a], [3f], [4b], [4e] electron acceptors,[5a] and dyes for bioimaging. [3d], [5b], [5c], [5d], [5e], [5f]…”
Section: Introductionmentioning
confidence: 99%